The Effect of Green Coffee Bean Extract on The Weight Rats with High Fat Diet - Arie Dwi Alristina; Annis Catur Adi; Rita Ismawati (Health Notions, 2018)
WHO declares that obesity is a global epidemic. In 2014, 39% of adults >18 years old were overweight and 13% had obesity. This research aims to determine the effect of green coffee extract on the weight rats fed high-fat diet. Method: This research is true experimental pre-post test with control group design. The animals were grouped into 5 groups, i.e., group1 (negative control), group2 (positive controls fed high-fat diet), group3 (high-fat diet and GCBE dose of 100 mg/kg BW), group4 (high-fat diet and GCBE with dose of 200 mg/Kg BW), group5 (highfat diet and GCBE dose of 400 mg/Kg BW). The obtained data were tested with one-way ANOVA followed by LSD analysis with α=0.05. Results: This research proves that green coffee bean extract with a dose of 100, 200 and 400 mg/kg BW can lower weight of rats with higt fat diet. Discussion: Green coffee extract contains active compound of chlorogenic acid that can increase AMPK activity so it has positive impact that can direct the result of metabolite substance, which is useful in decreasing fat synthesis. The high fat oxidation process results in decreased fat synthesis characterized by burning fat into energy thereby decreasing fat cells in adipose tissue.Keywords: Obesity, Body weight, Chlorogenic acid, Green coffee